Exposição ao btex e riscos à saúde em postos de combustível: revisão integrativa - Cafer, Clelia Regina (2023)
This is an integrative literature review with the objectives of identifying, critically evaluating and synthesizing the related scientific evidence on exposure to BTEX and health risks at fuel retail stations, as well as what has been done to monitor such exposure and future perspectives in relation to biofuels. The guiding question for the research was: What evidence is available in the literature on exposure and health risks related to BTEX in gas station workers? The databases Lilacs, PubMed, BVS, Medline, Scielo, Capes and Science Direct were selected to search for indexed primary studies in the last 05 years. Controlled and uncontrolled descriptors were selected according to each database. Of the 5835 studies found and considering the selection criteria, 3401 were excluded because they were not journal articles. Of the total of 183 eligible, 39 did not respond to the guiding question and 15 primary studies were included in the integrative review. A validated instrument was used for data extraction. Data analysis was descriptive and presented in three categories: Environmental occurrence and exposure by BTEX in CRP, workers’ health and biomonitoring and future perspectives: 2030 agenda and SDG’s. The development of this integrative literature review allowed, through the results obtained, to find the main evidence related to exposure to BTEX and health risks at fuel retail stations. In all categories, there is a need to train PRCV professionals in relation to the use of PPE throughout the work process.